Modeling of electron transport in phrosphorous doped single crystal CVD diamond - Lum, Madeleine Wan Ting. (2013)
Diamond as wide band gap material with extreme electrical and mechanical properties has huge potential for high voltage, high power, high speed, and high temperature power devices. Various p-type diamond devices have been achieved using Boron doping with 0.37 eV ionization energy and hole transport in diamond has been modeled. On the other hand, the shallowest conventional n-type diamond dopant is Phosphorus with deep level of 0.6eV. Despite of these, devices involving n-type diamond such as schottky diode and pn junction diode have been fabricated and measured experimentally. The objective in this study is to model electron transport in diamond empirically. Expected outcomes are incomplete ionization model for Phosphorus dopant in diamond, concentration and temperature dependent electron mobility model, and high field electron mobility model. The study will be conducted by curve fitting the values from experiment results and Monte Carlo simulation results reported in literature based on the respective physical models in TCAD Sentaurus. These models will be implemented in TCAD Sentaurus simulation software to simulate devices with n-type diamond.